Gram-negative bacterial sepsis, antimicrobial susceptibility pattern and treatment outcomes at two neonatal intensive care units in Addis Ababa, Ethiopia: A retrospective observational study. - Biniyam Tedla Mamo; Zelalem Tazu Bonger; Feyissa Regassa Senbato; Tadesse Eguale; Kibrewossen Kiflu Akililu; Samuel Muluye Welelaw; Eden Dagnachew Zeleke; Asrat Demtse; Turegne Assefa; Ruth Woldeyohannes Yirgu; Zelalem Mekuria; Joan-Miquel Balada-Llasat; et al. (PLoS ONE)
Background Neonatal sepsis is a leading cause of mortality and morbidity. To improve the clinical outcomes of neonates with sepsis, treatment should be based on bacteriological identification and antibiotic susceptibility. This study aims to assess the proportion of culture-positive gram-negative bacteria (GNB), the antibiotic susceptibility patterns, and treatment outcomes of neonatal sepsis at two neonatal intensive care units (NICUs) in Addis Ababa. Methods A retrospective observational study was conducted among gram-negative sepsis suspected neonates admitted at Zewditu Memorial Hospital and Tikur Anbessa Specialized Hospital NICUs from January to December 2023. All neonates who were suspected of having sepsis were included in this study. Standard microbiological culture and biochemical tests were used to identify bacterial species and the Kirby-Bauer disc diffusion assay using Mueller-Hinton agar was employed to test the antimicrobial susceptibility of bacterial isolates as per Clinical Laboratory Standard Institute guidelines. Descriptive statistics were used to describe the study variables. Bivariable and multivariable logistic regression analyses were used to identify the factors associated with the treatment outcomes of neonatal sepsis. A p-value < 0.05 was set for statistical significance. Results A total of 933 neonates were diagnosed with sepsis during the study period, of which 166 neonates were enrolled in the study for gram-negative sepsis: 84 (51%) were female and 97 (58%) had early onset sepsis. The median length of hospital stay was nine days with interquartile range of 16 days. The predominant GNB identified was Klebsiella spp. (n = 89; 49%), followed by Acinetobacter spp. (n = 38; 21%) and Escherichia coli (n = 19; 11%). In both hospitals, Klebsiella spp. was resistant to most of the routinely prescribed antibiotics: (n = 68; 89%) were resistant to ceftriaxone, (n = 56, 89%) cefepime and (n = 60; 75%) to gentamicin. Lower rates of resistance were recorded for other antibiotics such as ciprofloxacin (n = 12; 18%), ertapenem (n = 11; 16%), meropenem (n = 9; 13%), and amikacin (n = 3; 4%). A total of 92 (55%) neonates with the GNB isolated in the current study had multidrug-resistant (MDR) organisms. The study found that newborns with MDR infections were five times more likely to experience poor treatment outcomes compared to those with non-resistant strains (AOR, 5.23 95% CI [2.59, 11.11]). In addition, newborns who stayed less than seven days, compared to those who spent seven or more days in the hospital was four times (AOR: 4.16, 95% CI (2.0-9.01) more likely to experience poor health outcomes. Conclusion Klebsiella spp. was the most common GNB isolated from the NICUs. More than half neonatal sepsis was caused by MDR organisms and associated with significant poor treatment outcomes. high prevalence of MDR-gram-negative bacteremia is alarming and highlights the need for the implementation of routine surveillance and infection control measures to decrease morbidity and mortality and to combat the development of antimicrobial resistance.